Proust som indflydelsesmaskine - Thing, Neal Ashley Conrad (Passage - Tidsskrift for litteratur og kritik, 2015)
Neal Ashley Conrad Thing: “Proust as Engine of Influence” Marcel Proust’s main oeuvre, In Search of Lost Time (1913-27), is an engine of influence. The novel is, increasingly, affecting pratices of writing, ways of reasoning, and the concept of man. The influence of Proust’s novel has not been mapped in Denmark. Generalisations are thriving, but thanks to reception recearch it is possible to reveal Proust’s significant influence on Danish reviewers, critics and writers.